Perceived role and its enhancing factors among the village health volunteers regarding malaria control in rural myanmar - P Linn Aung; Tassanee Silawan; Tassanee Rawiworrakul; Myo Min (Wolters Kluwer Medknow Publications, 2018)
Background: Village health volunteers (VHVs) are key agents for malaria control in community. The Myanmar Medical Association-Malaria (MMA-Malaria) Project has promoted effective malaria control in endemic and high-risk townships by supporting roles of VHVs. Objectives: To assess the roles of VHVs on malaria control and factors enhancing their roles in rural Myanmar. Methods: A cross-sectional study was conducted in five townships where the MMA-Malaria Project has been implemented. One hundred and fifty VHVs were sampled from five townships by simple random sampling. Data were collected by trained interviewers using structured questionnaires, which covered sociodemographic, supportive, motivational factors, and roles of malaria control. Studied variables were described by proportions, means, and standard deviations and were analyzed for their association by odds ratio with 95% confidence interval and Chi-square tests. Results: Most of VHVs (96%) expected to demonstrate good roles on malaria control, but only 44.0% exhibited current roles at a good level. Factors enhancing their roles were female (P = 0.037), family income ≥50,001 kyat/month (P < 0.015), time serving as a volunteer 1-2 years (P = 0.006), good knowledge of malaria control (P < 0.001), good family support (P < 0.001), good community support (P < 0.001), and good motivational factors (P = 0.002). Conclusion: VHVs are key agents for malaria control in community. Most of VHVs expected to demonstrate good roles on malaria control, but less than half of them exhibited current roles at a good level. The systems and program for improving VHVs' knowledge, encouraging family and community support, and promoting motivation are essential for their better roles.